Closing-in Behavior and Parietal Lobe Deficits: Three Single Cases Exhibiting Different Manifestations of the Same Behavior - Ambron, Elisabetta; Piretti, Luca; Lunardelli, Alberta; Coslett, H. Branch (Frontiers in Psychology, 2018)
Closing-in behavior (CIB) is observed in copying tasks (graphic or gestural) when the copy is performed near or on the top of the model. This symptom has been classically considered to be a manifestation of constructional apraxia and is often associated with a visuospatial impairment. More recent work emphasizes the attentional and/or executive nature of the behavior and its association with frontal lobe dysfunction. We describe three patients in whom CIB was associated with posterior parietal deficits of different etiologies (stroke in Patient 1 and dementia in Patients 2 and 3). In copying figures, Patient 1 produced the shape with high accuracy but the rendering overlapped the model, while for Patients 2 and 3 the copies were distorted but overlapping or in close proximity to the target. In gesture imitation, Patient 2 performed the gestures toward the examiner’s space, while Patient 1 showed a peculiar form of CIB: when he was asked to place the ipsilesional arm in a position that mirrored the contralesional hand, Patient 1 moved his hand toward his contralesional hand. Patient 3 did not present gestural CIB. While CIB in Patient 1 was associated with selective deficits in executive functions and attention, additional visuospatial deficits were observed in Patients 2 and 3. The latter two patients showed a general visuoconstructional deficit. These case studies support a primary attentional account of CIB but also suggest that visuoconstructional impairments may contribute to the emergence of CIB, in some subjects. This evidence argues for different types of CIB with different cognitive and neural underpinnings. Furthermore, the data support the hypothesis of a differential involvement of fronto-parietal network in CIB.